1997
DOI: 10.1023/a:1006568324853
|View full text |Cite
|
Sign up to set email alerts
|

Comparing a Public and Private Sector NFP Program: Implications for NFP Expansion

Abstract: This paper synthesizes a six year collaboration between a natural family planning (NFP) non-governmental organization (NGO) and the National Health Service of the Emilia Romagna region in Italy. It also compares the public program experience with NFP services provided in the private sector in the adjacent region of Veneto. Midwives provided NFP services in government family health clinics while in the private sector NFP was taught by non-health laypersons in a church-based facility. The populations served by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…A broader population might benefit from access to NFP. Education about NFP by public clinics that offer multiple methods has been attempted in Italy (Girotto et al, 1997) and the Philippines (Infantado, 1997) with mixed results. Further, NFP counseling is time consuming and therefore it may be difficult for clinicians to offer, therefore necessitating referral to a certified NFP instructor.…”
Section: Discussionmentioning
confidence: 99%
“…A broader population might benefit from access to NFP. Education about NFP by public clinics that offer multiple methods has been attempted in Italy (Girotto et al, 1997) and the Philippines (Infantado, 1997) with mixed results. Further, NFP counseling is time consuming and therefore it may be difficult for clinicians to offer, therefore necessitating referral to a certified NFP instructor.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the perceived relative ineffectiveness of NFP, providers and potential users often view the periodic abstinence required for its use as a negative (18,23–25); thus, providers of family‐planning methods who have a negative view of periodic abstinence may be less likely to prescribe any method that requires it. Although this study did not ask about family planning use among its CNM respondents, a recent study of female physicians showed that NFP was used in only about 2% of the sample (31), which corresponds to a study that indicates usage of NFP as a primary method of family planning in only about 2–3% of women in the United States (21).…”
Section: Resultsmentioning
confidence: 99%
“…As with LAM, the reason NFP is not used by more couples is probably due to lifestyle, personal choice, and lack of knowledge. Another reason may be that influential health care professionals have little knowledge of NFP and do not promote or trust its use as a means of child spacing, a supposition confirmed by several studies of physicians and nurses (22–26). However, when health professionals provide women with information on NFP in a positive way, 22–37% would likely or very likely use NFP to either avoid or achieve pregnancy (27,28).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Doring, Baur, and Frank-Herrmann (1990) conducted telephone interviews of 229 general practitioners and 237 gynecologists from Germany and discovered that only 6% of them prescribed NFP as the main method of family planning and only 10% recommended the NFP method. One hundred twenty-one Italian family practice physicians responded to a questionnaire on the use of contraception and NFP in a study by Girotto et al (1997). Findings indicated that more than 50% of the physicians knew little about NFP methods, 91.8% never or rarely recommended them, and only 8% would prescribe NFP for their patients.…”
Section: Knowledge and Use Of Nfp Among Health Care Professionalsmentioning
confidence: 99%